A case of spontaneous hypoglycemia (BIRDEM Medical Journal, 2021)
We describe a case of systemic lupus erythematosus with POEMS syndrome presenting as spontaneous hypoglycemia. A 58-year-old female suffered repeated episodes of hypoglycemia. During thesehypoglycemic episodes, her postprandial insulin level was inappropriately high. Further blood tests revealed the presence of antinuclear antibodies, anti-double-stranded DNA antibodies,low C4level.Altered albumin-globulin ratio,monoclonal gammopathy (IgG LAMBDA), polyneuropathy and organomegaly lead to suspicion of concurrent presence of POEMS syndrome.Bone marrow examination revealed plasma cell dyscrasia and plasmacytoma in trephine biopsy confirmed the diagnosis.Here, we emphasize on autoimmune cause of hypoglycemia.BIRDEM Med J 2022; 12(1): 70-73